Relationship Churning and Desistance From Intimate Abuse - Halpern-Meekin, Sarah (Journal of interpersonal violence, 2021)
It is essential to understand how desistance from intimate abuse occurs so it can be facilitated for those experiencing it. Recognizing the category of churning relationships—in which partners separate and reunite—gives us analytic leverage in identifying the relationship dynamics that predict abuse desistance. Using data from the Fragile Families and Child Wellbeing Study, a longitudinal survey of parents in urban areas, we compare desistance among churners (who experience a breakup only) with those who repartner (who experience a breakup and a new partnership) and those who are stably together (who experience neither a breakup nor a new partnership). We examine whether abuse desistance patterns are distinct for those who breakup and reconcile versus those who breakup and form new partnerships—that is, we can separate out the association between abuse desistance and the breakup versus the new partnership. We find that, among those with a history of intimate abuse, churners and those who later repartner are overrepresented. However, among those who do experience abuse, the repartnered are most likely to experience desistance from intimate abuse, controlling for individual sociodemographic characteristics. In breaking up and entering a new relationship, the repartnered may be most successful in developing a healthier relationship dynamic than the churners who reunite with one another.